The Role Of Agency Services In Serving Clearance In And Out Of Ship With Manual System at PT. Bama Putra Sukses Bogor - Rizki Prayoga Sinulingga; Aja Avriana Said (Jurnal Transformasi Bisnis Digital, 2025)
Shipping companies have an important role in providing services to ships visiting a port. Shipping companies appointed as agents are the parties that will be responsible for taking care of everything so that the ships they represent can dock properly, on time, and smoothly in carrying out their activities at the port. Ship agency services are needed to assist the process of clearance in and out of ships at a port in order to create conducive ship activities. This study was conducted to determine the role of agencies in serving the clearance in and out process and the factors that hinder the ship clearance process using a manual system at PT. Bama Putra Sukses Bogor. This study uses a qualitative approach with a descriptive type. Data collection for this study was carried out using observation, interview, and documentation techniques. The results of this study showed that the role of agencies in serving ship clearance in and out with a manual system at PT. Bama Putra Sukses Bogor is a series of ship clearance processes from ship entry to ship exit. Agents play a role in providing their services to ship owners in ship clearance services that are oriented towards managing ship documents in order to facilitate the loading and unloading process. Factors that hinder the clearance in and out process at PT. Bama Putra Sukses consist of expired documents and problems waiting for the destination port or called waiting next port.